Development of a market entry and marketing strategy for Germany : internationalization of the portuguese swimwear startup Turquesa Beach - Schwäble, Moritz Christoph (2018)
Turquesa Beach an early startup for premium children swimwear wants to expand internationally to Germany. It sought the help from the master consulting project to analyze the swimwear market, assess the costs of entering, find the right marketing and entry strategy. The literature review analyzed the current state of the academic world on internationalization of new ventures and how networks affect the internationalization process. This is followed by current findings of researchers on digital marketing and the best practices. The analysis part characterizes the German swimwear market, compares different entry and marketing strategies. Based on the findings and the assessment of the firm, recommendations were drawn on how Turquesa Beach should proceed with its internationalization to Germany.